Mandibular Growth of Untreated Patients with Skeletal Class II Malocclusion - Ayşe Tuba Altuğ-Ataç; Öykü Nebioğlu-Dalcı (Galenos Yayinevi, 2006)
The purpose of the study is to compare the mandibular growth of the skeletal Class II individuals with increased overjet and skeletal Class II individuals with normal overjet-overbite relations, and to define if the growth of the mandible is effected by the position of the maxillary incisors. The patients included in the study were divided into three groups. The first group consisted of individuals (female: 11, male: 8, total: 19; mean age 13.2 years) with skeletal Class II + increased overjet, the second group consisted of individuals (female: 9, male: 10, total: 19; mean age 14.1 years) with skeletal Class II + normal incisor relations and the third group, which acted as the control group consisted of individuals (female: 12 , male: 5, total: 17; mean age 13.1 years) with skeletal Class I relationship. The measurements were done on pre-treatment/pre-control lateral cephalometric radiographs. In the study, the descriptive measurements (SNA, SNB, ANB, overjet, overbite, SN/Go-Gn) and measurements that define the size and position of the mandible (B-VR, Pg-VR, S-Go, Co-Go, Co-Gn, Go-Gn) were evaluated. The differences between the groups were evaluated by Analysis of Variance and Duncan's tests. There were statistically significant differences between SNB, ANB, SN/GoGn and overjet (descriptive parameters). Furthermore, Pg-VR, Go-Gn (p<0.05); Co-Go (p<0.01) and Co-Gn (p<0.001) showed statistically significant differences between group 1 and group 2; and group 2 and control group. The results of the study supported that the position of the maxillary incisors plays a role in the growth of the mandible. The linear measurements of the mandible were smaller in the patients whose mandibles were restricted by the maxillary incisors.